Estudo da influência de íons titânio e cobalto nas propriedades magnéticas e absorvedoras de ondas eletromagnéticas de hexaferrita de bário - Yasuda, Márcio Tsuyoshi (2008)
In this work Cobalt and Titanium doped Barium hexaferrites were synthesized by the ceramic method in order to study their use as electromagnetic absorbing materials in high frequencies. The dopants were used individually (Ti and Co) and with both simultaneously (CT). Ceramic characteristics and magnetic properties of calcined powders, as well as of their pellets sintered in electric and microwave furnaces were evaluated. For the high frequency permeability measurements, hexaferrites ring-shaped sintered and ring-shaped composites with the hexaferrite powders and epoxi resin were produced. Barium hexaferrite powder (BaM) presented 3.45 kOe of coercivity and the same synthesizing conditions were used in all hexaferrites with dopant atomic fractions of 0,2; 0,4; 0,6; 0,8; and 1,0. In Ti hexaferrites (BaFe12-xTixO19) microstructures there were BaFe2O4, Fe2O3 and Ba3Fe10TiO20 phases and they presented coercivities between 1,53 and 1,04 kOe. Co hexaferrites (BaFe12- xCoxO19) microstructures showed W, Y and Z hexaferrites types phases, with coercivities between 0,70 and 0,21 kOe. In CT hexaferrites (BaFe12-2xCoxTixO19) it was presented CoFe2O4 phase, with coercivities between 0,09 and 1,06 kOe was presented. Most of the pellets sintered in microwave furnace had apparent densities close to those of the pellets sintered in electric furnace and their coercivities were higher or equal. The grains heterogeneity increased with dopant quantities and the Ti microstructures presented more quantity of M type hexaferrites in comparison to other samples. The ring-shaped sintered samples of BaM, Ti and CT hexaferrites showed ferrimagnetic ressonance peaks in 110 MHz and 780 GHz. In Co hexaferrites the presence of hexaferrites different from M type contributed to the different tangent loss in comparison to other hexaferrites. The tangent loss of composites showed the same peaks observed in the ring-shaped sintered samples but with smaller intensities. These composites showed absorption loss up to 20 dB in 12 GHz too.